Evaluación del estado actual de degradación del suelo en agroecosistemas de cacao y pasto en la granja Santa Inés - Romero Macas, Dianney Jannina (2017)
The soil is a natural body composed of air, water, minerals and organic matter, necessary for the life of the plants; however, its systematic and accelerated degradation is a problem at global and national levels. Currently, the increase of the population generates more demand for food by what man intensifies agricultural work on the ground. A problem of degradation is which causes a decrease in the percentage of porosity of the soil aeration, affecting the exchange of gases, moisture retention and to the development of the roots. The aim of the research was to determine the current state of degradation of soils under continued cultivation of cocoa and pasture by the characterization of its physical and chemical properties in agroecosystems of the farm Santa Inés, Academic Unit of Agricultural Sciences belonging to the Technical University of Machala El Oro province. For this purpose, sampling points were established for each production system, in which soil samples were taken to 0-15, 15-30 and 30-45 cm depth from the established protocol. The system was used wood as a witness of comparison. The analytical determinations were carried out in the Laboratory of soils of the Academic Unit, which evaluated the following physical properties: Color of soil (wet and dry) through the use of the Table Munsell, texture by the hydrometer method of Bouyoucus and textural class was determined using the diagram of texture. To calculate the porosity of the soil previously real density was determined by the method of the pycnometer and apparent density by the method of the lump. Within the Chemical Properties pH was determined through the use of peachimetro in a relationship 1:2.5 soil/water, for electrical conductivity was used the method of Conductivimetro, for organic carbon content of the light fraction, thick and total with the method of Walkley & Black. The results show that in the agroecosystem grass were found the highest values of density in the first 15 cm, different statistically to the cocoa and forest, a condition that is related to the trampling of cattle in conditions of excessive moisture, generating layers compacted, poor root development, poor drainage, inadequate aeration, elements that favor the processes degradativos, with respect to pH in soil in grass is classified as alkaline to difference of the agroecosystems of cocoa and forest that is in a state next to the neutrality, this condition of salinity affects the development of crops. The property that more influence has on the physical and chemical properties of the soil organic matter content and total organic carbon, which in the agroecosystem grass presented lower values compared to cocoa and forest that have similar content by its accumulation of plant residues in the surface layer and deepens in the profile this content decreases, so that soil degradation in a productive system is closely related to the content of organic matter and total carbon